PERANAN PERENCANAAN, PEMELIHARAAN DAN PENGHAPUSAN PERALATAN KANTOR TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN GRESIK - SEPTIA EKAWATI, LILY (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT Activities office has a close relationship with the office equipment as an important means to generate employment office. Planning office equipment is the first step to hold the office equipment. The study is descriptive quantitative research. The data collection techniques were questionnaires, documentation and interview. The population was 85 people and the sample was 50 people, taken by purposive sampling technique. The data analysis techniques included validity, reliability test, and multiple linier regression analysis. The findings of this study were the condition of the planning, maintenance, removal and performance of employees is high and planning office equipment partially contribute strongly to employee performance, maintenance of office equipment partially contribute strongly to the performance of employee, elimination of weak partially contribute to employee performance and planning, maintenance, elimination simultaneously strong role on the performance of employees.Keywords: Planning, Maintenance, Elimination Office Equipment and Employee Performance.